ANALISIS KANDUNGAN SiO2 PADA BATUAN GREEN TUFF DENGAN METODE GRAVIMETRIK - Nurul Fuadi; Ayu Annisa Amir (Universitas Negeri Gorontalo, 2020)
Research has been conducted on the content of Silica dioxide (SiO2) in Green Tuff rocks from Bone of South Sulawesi Province. This Green Tuff rock is a type of sedimentary rock formed from volcanic ash released from a pit during a volcanic eruption. This research uses the gravimetric method which is analytical chemical method by weighing the sample that has been melted as much as 0.5 grams then adding enough distilled water, 10 ml of HCl and 5 ml of HNO3, after that it is heated to dry and added 5 mL of HCl. Reheat until the volume becomes half of the initial volume and added distilled water afterwards, cooled and filtered. The purpose of adding HCl and HNO3 is so that the silica content can be separated from the impurities so that a larger crystal-shaped silica precipitate and a yellowish-colored solution containing impurities are present in the precipitate. So that in this study the results of the analysis of the content of Silica dioxide (SiO2) of 76.50%.